Peran Harga CPO dan Volume Penjualan dalam Fluktuasi Harga Saham Perusahaan Perkebunan Kelapa Sawit di Bursa Efek Indonesia - Sari, Dewi Maya; Ardian; Wilda, Hurul (Jurnal EMT KITA, 2025)
This study aims to analyze the impact of Crude Palm Oil (CPO) prices and sales volume on stock price changes in palm oil plantation companies on the Indonesia Stock Exchange. This research employs a quantitative approach using multiple linear regression analysis to examine the relationship between variables. The research sample consists of 8 companies over the 2020 to 2023 period, with a total of 32 observations. The sample determined using purposive sampling based on the criteria of reporting sales volume data and annual financial statements during the observation period. The research results indicate that CPO price have a positive band significant effect on stock prices, while sales volume has a negative byt insignificant effect. These findings confirm that the stock price movements of palm oil plantation companies in Indonesia are more influenced by global CPO price dynamics that by the companies’ own sales volumes. The practical implications of this research are beneficial for investors and company management in formulating investment decisions and business strategies that are more adaptive to CPO price fluctuations. This Study has limitations in term of relatively short observation period and has not yet taken into account other variables such as exchange rates, interest rates, or ESG (Enviromental, Social, and Governance) issues, which are highly relevant in the palm oil plantation industry.
Keywords: CPO Prices; Sales Volume; Stock Prices; Palm Oil Companies; Indonesia Stock Exchange